Comparative study of tympanoplasty with or without cortical mastoidectomy - Islam, Md Tauhidul; Rafiquzzaman, Md (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: Tympanoplasty with or without cortical mastoidectomy is the subject of debate amongst different otolaryngologists. One theory suggests that tympanoplasty type-I which combined with cortical mastoidectomy in wet or discharging ear is beneficial. Other theory suggests that cortical mastoidectomy adjunct with tympanoplasty type-I, has no significant effects on surgical outcome in any condition of dry or wet ear in tubotympanic variety of CSOM. Aim: The purpose of this study is to compare the surgical outcome of type-I tympanoplasty with or without cortical mastoidectomy. Methods: It is a retrospective, observational, multicentre study conducted in between July 2003 to July 2013 amongst 258 patients of uncomplicated tubotympanic variety of chronic suppurative otits media with age ranging from 18 years to 55 years. 140 patients (54%) were having history of ear discharge (Group-I) and remaining 118 patients (46%), having no complaints of ear discharge (Group-II) within 3 months prior to surgery. 50% of each group were operated with tympanoplasty type-I only and 50% of each group was operated with tympanoplasty type-I with cortical mastoidectomy. Outcome of surgical procedures in different groups were analyzed in terms of graft uptake and hearing improvement. Results: Out of 140 patients with discharging ear, only tympanoplasty procedure (n=70) resulted in successful graft taking in 62 patients (88.6%) and the hearing level within 20dB were achieved in 57 persons (81.4%). Tympanoplasty with cortical mastoidectomy (n=70) resulted in successful graft taking in 61 patients (87%) and the postoperative 69 JAFMC Bangladesh. Vol 10, No 1 (June) 2014 hearing level within 20dB were found in 56 persons (80 %). Out of 118 patients with dry ear, only tympanoplasty procedure (n=59) resulted in successful graft taking in 54 patients (91.5%) and postoperative hearing level within 20dB were achieved in 48 persons (81.36%). Tympanoplasty with cortical mastoidectomy (n=59) resulted in successful graft taking in 53 patients (89.8 %) and the postoperative hearing level within 20dB were achieved in 47 persons (79.7%). Comparison of results in both procedures in dry and wet ear showed no significant statistical difference. Conclusion: Cortical mastoidectomy is not proved to be mandatory or effectively helpful with type-I tympanoplasty for uncomplicated chronic suppurative otitis media, irrespective of its dry or discharging status. DOI: http://dx.doi.org/10.3329/jafmc.v10i1.22928 Journal of Armed Forces Medical College Bangladesh Vol.10(1) 2014